1997
DOI: 10.1175/1520-0450-36.6.792
|View full text |Cite
|
Sign up to set email alerts
|

Variability of SO=4, Total Sulfate, NO−3, and Total Nitrate Scavenging Ratios for the Frontal Boundary Study

Abstract: Precipitation and air concentration data collected during a U.S. Department of Energy-sponsored Frontal Boundary Study (FBS) were used to calculate scavenging ratios. The precipitation data were collected on a 100 km ϫ 100 km surface grid containing 36 sampling sites, while the air concentration data were collected by aircraft. Radar and rawinsonde data were used to position the aircraft into the air mass feeding the precipitation. The coordination of the aircraft data with surface precipitation data allows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The scavenging ratios of sulphate ranged between 1.0×10 6 and 17.0×10 6 which are comparable to values as reported for other sites (KasperGiebl, 1999;Davis et al, 1997). Relatively lower k values are obtained for 142 and 144JD, when the POSS consistently reported rain as the precipitation type.…”
Section: Chemical Species In Precipitationsupporting
confidence: 84%
See 2 more Smart Citations
“…The scavenging ratios of sulphate ranged between 1.0×10 6 and 17.0×10 6 which are comparable to values as reported for other sites (KasperGiebl, 1999;Davis et al, 1997). Relatively lower k values are obtained for 142 and 144JD, when the POSS consistently reported rain as the precipitation type.…”
Section: Chemical Species In Precipitationsupporting
confidence: 84%
“…Although all the trends in aerosol particles mentioned above may be explained by the temporal meteorological conditions, it should be noted that the time period of this campaign included the period of the aerosol transition from spring-type to summer-type, as indicated by Engvall et al (2008). Therefore, it is reasonable to regard the decrease in aerosol loading in this study as being partly a reflection of the aerosol transition processes occurring in the arctic region around this time period of the year.…”
Section: Meteorological Conditions During the Campaignmentioning
confidence: 96%
See 1 more Smart Citation
“…However, Davis et al (1997) reported that scavenging ratios obtained from surface concentration data are in a comparable range with those obtained from aircraft measurements. Scavenging ratio depends on the particle size distribution, precipitation rates and the chemical characteristics of the particle.…”
Section: Scheme Iv: Scavenging Ratiomentioning
confidence: 73%
“…Dorling et al, 1992;Cana-Cascalar, 2002), and spatial-pattern analyses of atmospheric circulation (Davies et al, 1991;Yarnal, 1991Yarnal, , 1993Dorling et al, 1992;Lamb, 2003, 2005). Typical studies employ the ionic concentrations, rather than the deposition flux itself, because precipitation composition is closely linked to the concentrations of precursors in air (Engelman, 1971;Davis et al, 1997;Hicks, 2005).…”
Section: Introductionmentioning
confidence: 99%